Personality Traits and Physical Complaints in Patients With Acromegaly: A Cross Sectional Multi-Center Study With Analysis of Influencing Factors - Zimmermann, Anca; Zwerenz, Rüdiger; Droste, Michael; Schöfl, Christof; Strasburger, Christian J.; Plöckinger, Ursula; Ziagaki, Athanasia; Honegger, Jürgen; Dixius, Anne; Millaku, Bledar; Toenges, Gerrit; Beutel, Manfred E.; et al. (Frontiers in Endocrinology, 2018)
Objective: Acromegalic patients display a distinct neuropsychological profile and suffer from chronic physical complaints. We aimed to investigate in more detail these aspects in acromegalic patients, dependent on influencing factors like disease activity, age, sex, chronic medication, surgery, pituitary radiation, pituitary insufficiency and comorbidities. Design: Cross sectional, multicentric. Methods: 129 patients (M/W 65/64, 58.3±12.7 ys., 53/76 with active/controlled disease). Acromegalic patients completed the following inventories: NEO-FFI, IIP-D, and the Giessen Complaints List (GBB-24), after written informed consent. Age, sex, IGF-1 concentrations, comorbidities, treatment modalities and pituitary insufficiency were documented. Results: Acromegalic patients or specific patient-subgroups were more agreeable, neurotic, exploitable/permissive, introverted/socially avoidant, non-assertive/insecure, nurturant and less open to experience, cold/denying, domineering, compared to normal values from the healthy population (controls). Multivariable analysis demonstrated that these overall results were due to the specific patient subgroups as patients on chronic medication, with arthrosis and pituitary insufficiency. Disease activity was only associated with the trait nurturant. Higher scores for introversion were associated with arthrosis. Lower domineering was independent of any disease- or treatment related variable or comorbidity. The GBB inventory showed overall higher scores in patients, with higher scores for exhaustion and general complaints being associated with pituitary insufficiency, coronary heart disease and history of malignancy in the multivariable analysis. Joint complaints were independent of any disease- or treatment- related variable. Conclusions: We define new aspects of a distinct neuropsychological profile in patients with acromegaly, which are largely independent of disease activity. Chronic physical complaints are more pronounced in patients than in controls, with exhaustion and general complaints showing no association with disease activity.